(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2020)
Climate change is imposing significant stresses upon agriculture at a time when more food is required for an increasing world population. The breeding of stress-resistant crops or their genetic engineering is possible responses to these difficulties. Intellectual Property Rights (IPRs) have been identified as a means for incentivizing agricultural innovations. The international IPR regime based upon the World Trade Organization (WTO) Agreement on Trade-related Aspects of Intellectual Property Rights (TRIPS) establishes a global intellectual property regime which obliges states to provide legal protection for newly developed plant varieties and also enables the patenting and therefore commoditization of stress-tolerant DNA in the 177 member states of the WTO.